EFFECT OF PROBLEM BASED LEARNING AND MODEL CRITICAL THINKING ABILITY TO PROBLEM SOLVING SKILLS - Unita S. Zuliani Nasution; Sahyar .; Makmur Sirait (Jurnal Pendidikan Fisika, 2016)
The purposes of this research were to analyze the different between physic resolving problem ability by using problem based learning model and direct instruction model, the different of physic resolving problem ability between the students that have critical thinking ability upper the average and the students that have critical thinking ability under the average, and the interaction of problem based learning model toward critical thinking ability and students’ physic resolving problem ability. This research was quasy experimental research that use critical thinking ability tests and physic resolving problem ability tests as the instruments. Result of the research showed that the students’ physic resolving problem ability by using problem based learning model was better than by using direct instruction model, students’ physic resolving problem ability and critical thinking ability upper the average showed better different and result than students’ critical thinking ability under the average, besides there was an interaction between problem based learning model and critical thinking ability in improving students’ physic resolving problem ability.